Determinasi Keputusan Wakif Berwakaf Uang: Peran Literasi, Lingkungan Sosial, dan Akses Informasi pada Dompet Dhuafa Waspada - Juwita, Tri Asda; Manik, M. Rikwan Effendi Salam; Agus, Rizal; Zuhirsyan, Muhamad; Nasution, Anriza Witi (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of waqf literacy, social environmental factors, and information access on waqif decisions to donate cash waqf at Dompet Dhuafa Waspada, Medan City. The waqif’s decision was designated as the dependent variable, while the independent variables consisted of waqf literacy, social environment, and information access. A total of 55 respondents participated in the study. A quantitative approach was employed. Data were analyzed using multiple linear regression, the simultaneous F-test, the coefficient of determination (R²), and the partial t-test at a 5% significance level (α = 0.05). Data processing was carried out using SPSS version 26. The coefficient of determination (R²) value of 0.455 indicates that the independent variables explain 45.5% of the variation in the dependent variable, while the remaining 54.5% is influenced by other unexamined factors. The results show that waqf literacy and social environment have a significant partial effect on waqif decisions to donate cash waqf, whereas information access does not have a significant effect. Overall, waqf literacy, social environment, and information access collectively have a significant influence on waqif decisions to donate cash waqf at Dompet Dhuafa Waspada, Medan City.
Keywords: Waqf Literacy; Social Environment; Access to Information; Waqif Decision